2018
DOI: 10.1002/casp.2348
|View full text |Cite
|
Sign up to set email alerts
|

Conducting community‐based participatory research in an urban Malaysian community: Lessons learned and challenges in establishing partnerships

Abstract: This paper presents the process of how partnerships are established between an urban residential community and an academic institution in Malaysia by employing community‐based participatory research, which involves researchers, community members, and organizational representatives as coresearchers. The research process encompasses colearning, power sharing, and coconstructing of knowledge, with the community members driving the research direction. The research paradigm is grounded on conducting research with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The authors identify essential elements of effective participation including working together and creating opportunities to be engaged at different stages of research. Teoh et al (2018) report two key challenges in co-methods work, firstly the potential for hierarchy within the team and secondly power dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors identify essential elements of effective participation including working together and creating opportunities to be engaged at different stages of research. Teoh et al (2018) report two key challenges in co-methods work, firstly the potential for hierarchy within the team and secondly power dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…These were often small extracts which we were drawn to and which offered a key to understanding what matters. Beyond existing principles(Aner, 2016;Arnstein, 1969;Teoh et al, 2018) we have identified gems of good practice and from these derived pragmatic recommendations for enhancing future C-MW with older people. Preparation is key, researchers need to consider why they are choosing to use C-MW and then articulate this to older people including discussion of expectations and limitations.…”
mentioning
confidence: 99%